Integrated compaction control based on the motion behavior of a deep vibrator. (May 2021) - Nagy, Peter; Pistrol, Johannes; Kopf, Fritz; Adam, Dietmar
Abstract: Deep vibro compaction (vibroflotation) is a widely-used ground improvement technique in granular soils. During the compaction process, the vibrator body is in constant interaction with the compacted soil. The changing ground conditions influence the motion behavior, making it possible to use the deep vibrator not only as a compaction device but also as a measurement tool. Within the scope of the current study, large-scale experimental field tests were realized to monitor the motion behavior during the compaction process. This paper discusses the concept and the results of the experimental investigations. Based on the test results, the vibrator motion is shown, highlighting the influence of the contact stress between vibrator cone and soil on the motion behavior. An analytical model is used to investigate the relationship between the actual soil stiffness and the vibrator motion. A working hypothesis is presented, which allowed identifying dominant soil mechanical processes leading to the compaction effect in the soil. Finally, the potential of the findings for developing a work- and vibrator-integrated compaction control system is shown. Such a procedure results in a homogenous compaction effect, exploiting the potential of the compaction device while avoiding its overloading.